Substance Abuse Mortality and Socioeconomics: A Comparative Study of Istanbul’s Districts - Şahin, Hüseyin Çağrı; Boylu, Muhammed Emin; Acar, Burak; Can, Abdulkadir; Çakır, Halit; Yaman, Ömer Miraç (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: The fight against substance use disorders, which have been on the rise in recent years, requires a multidisciplinary approach. The factors that cause addiction, environmental factors that enable substance access, and the resulting harm from substance use are intertwined. As per the 2021 data released by the Istanbul Morgue Specialization Department of the Council of Forensic Medicine, drug or stimulant use caused 1.7% of the 5458 autopsies conducted. In our research, deaths resulting from polysubstance use are the most prevalent, with amphetamine derivatives being the most frequently detected substance. The rise in fatalities associated with amphetamine derivatives and their easy accessibility pose a significant public health concern. Based on these findings, it is crucial to focus on the environmental and economic factors that support the use of these substances to control access to amphetamine derivatives. Additionally, people with substance abuse problems are isolated due to social isolation. This situation makes it difficult for them to access addiction treatment and prevents them from receiving emergency medical intervention in the event of an overdose. In this context, it is advisable to adopt a multidisciplinary approach and to develop a comprehensive intervention strategy in cooperation with the health, education, and security sectors.
Keywords: Death; drug; Istanbul; polydrug; polysubstance; substance abuse